Ascorbate peroxidase plays an important role in photoacclimation in the extremophilic red alga Cyanidiococcus yangmingshanensis - Fu, Han-Yi; Wang, Ming-Wei (Frontiers in Plant Science, 2023)
Acidothermophilic cyanidiophytes in natural habitats can survive under a wide variety of light regimes, and the exploration and elucidation of their long-term photoacclimation mechanisms promises great potential for further biotechnological applications. Ascorbic acid was previously identified as an important protectant against high light stress in Galdieria partita under mixotrophic conditions, yet whether ascorbic acid and its related enzymatic reactive oxygen species (ROS) scavenging system was crucial in photoacclimation for photoautotrophic cyanidiophytes was unclear. The significance of ascorbic acid and related ROS scavenging and antioxidant regenerating enzymes in photoacclimation in the extremophilic red alga Cyanidiococcus yangmingshanensis was investigated. Accumulation of ascorbic acid and activation of the ascorbate-related enzymatic ROS scavenging system characterized the photoacclimation response after cells were transferred from a low light condition at 20 μmol photons m–2 s–1 to various light conditions in the range from 0 to 1000 μmol photons m–2 s–1. The activity of ascorbate peroxidase (APX) was most remarkably enhanced with increasing light intensities and illumination periods among the enzymatic activities being measured. Light-dependent regulation of the APX activity was associated with transcriptional regulation of the chloroplast-targeted APX gene. The important role of the APX activity in photoacclimation was evidenced by the effect of the APX inhibitors on the photosystem II activity and the chlorophyll a content under the high light condition at 1000 μmol photons m–2 s–1. Our findings provide a mechanistic explanation for the acclimation of C. yangmingshanensis to a wide range of light regimes in natural habitats.